Assessment of Virtual Reality technology as a tool to enhance beauty and skincare e-commerce targeting Gen X, Millennials and Gen Z in Dubai, United Arab Emirates - Almomani, Suzan (2020)
This paper explores whether a virtual shopping experience using immersive VR technologies can enhance and possibly substitute an in-store presence of a consumer shopping for beauty and skincare products. Differences in age groups directly affect consumers’ approach towards shopping and lead their shopping patterns while browsing for beauty and skincare products. Three generational cohorts including Gen Z aged between (7-22 years old), Millennials aged between (23-38 years old) and Gen X aged between (39-54 years old) were selected for the purpose of this study. Each group consisted of 10 female participants, thus a total of 30 responses were analysed and studied. VR experiment combined with survey research method was adopted to develop an understanding of how generational cohorts are unique in the way they perceive and engage with physical and online shopping. MAC cosmetics hypothetical virtual store was designed in 3D using SketchUp program and launched as a VR experiment using a plugin called Enscape. Three surveys in a 5-point Likert scale format were distributed among all participants to analyse the positive potential of introducing VR features into beauty and skincare e-commerce. First survey collected general feedback about online shopping and VR, second survey gathered responses about MAC cosmetics current physical stores’ design and the third survey was taken to record the feedback after undergoing the MAC cosmetics virtual store experiment. This research found that generational differences affect the acceptance and engagement levels with novel technological advancements in retail. Millennials were observed to be the most educated about the progression of VR technology into retail in general. Overall, all participants had positive feedback about the virtual store experience, however Gen X had reported difficulties in navigation and needed more human assistance during the experiment. No motion sickness was reported and all participants were interested to shop in future virtual stores equipped with features like virtual mirrors and digital skin analysis with Gen Z being the most supportive and excited.